The Role of Robot-Assisted Technique in Treating Adult Degenerative Scoliosis with Circumferential Minimal Invasive Correction Surgery – A Retrospective Analysis of 51 Consecutive Cases - Zhang Q; Chen Z; Lin Y; Zhang X; Wu W; Liang Y (Orthopedic Research and Reviews)
Qiang Zhang,* Zhe Chen,* Yazhou Lin, Xingkai Zhang, Wenjian Wu,* Yu Liang* Department of Orthopedics, Ruijin Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, 200025, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Liang, Department of Orthopedics, Ruijin Hospital, Shanghai Jiaotong University School of Medicine, 197 Ruijin Er Road, Shanghai, 200025, People’s Republic of China, Email hugoliang@126.com Wenjian Wu, Department of Orthopedics, Ruijin Hospital, Shanghai Jiaotong University School of Medicine, 197 Ruijin Er Road, Shanghai, 200025, People’s Republic of China, Email drwuwenjian@126.comStudy Design: Retrospective chart review.Objective: This study aims to investigate the application of robots in treating adult degenerative scoliosis (ADS) with circumferential minimal invasive surgery (cMIS).Background: The cMIS is useful but faces a lot of challenges in correcting ADS. One of the most important challenges is the difficulty in screw placement. Robot-assisted technique demonstrates lots of advantages but the data about its application in treating ADS is limited in literatures.Methods: A total of 51 cases diagnosed with ADS were retrospectively analyzed. All patients underwent cMIS technique with staged surgeries (OLIF and PPS fixation). Group A enrolled 21 patients and performed robot-assisted technique. Group B enrolled 30 patients and performed fluoroscopy guided technique. Clinical outcomes like the operation time, radiation exposure, pressure curve and post-operation VAS score were recorded. 3D-CT scan was also performed to evaluate the accuracy of the screws.Results: The average preparation time were much higher in group A (23.4 ± 2.8 vs 3.1 ± 1.0 min, p < 0.0001). But the total operation time was similar (62.7 ± 12.5 vs 55.7 ± 20.6 min, p = 0.174). The average fluoroscopic scan number were 9.4 ± 1.7 in group A, much lower than that of group A (27.7 ± 5.9, p < 0.001). No statistical difference was found with the VAS scale between the groups (p = 0.631). No matter considers only screws of grade A as perfect screws (81.5% vs 73.8%) or considers both grade A and B as acceptable screws (93.8% vs 87.7%), group A demonstrated significant higher screw accuracy (p = 0.038, p = 0.018, respectively). Also, the robots demonstrated significant less facet joint violence (p < 0.0001), larger inward tilt angle (p < 0.0001), and longer screw length (p = 0.0008).Conclusion: The robot-assisted technique demonstrated significant advantages like higher pedicle screw accuracy, better trajectory, less radiation exposure, but similar operation time compared with fluoroscopy guided technique in treating ADS with CMIS.Keywords: adult degenerative scoliosis, circumferential minimal invasive surgery, robotics, OrthBot, pressure curve